2005
DOI: 10.1149/1.1883236
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Kinetic Modeling of the AlCl[sub 3] Decomposition in the AlCl[sub 3]-CO[sub 2]-H[sub 2]-HCl System for a Hot-Wall CVD Reactor

Abstract: For a specific set of conditions applied in experimental hot-wall reactor investigations for depositing ␣-Al 2 O 3 from precursor gas mixtures containing AlCl 3 , kinetic modelling of the gas-phase reactions was carried out on the basis of rate parameters collected or estimated by Catoire and Swihart. Calculations are presented for upward flow rates of 200, 20, 0.41, and 0.08 slh, a vertical tube reactor ͑27 mm id͒ with a 450 mm isothermal zone ͑1050°C͒ and with varying concentrations of AlCl 3 , CO 2 , H 2 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…For example, a recent kinetic study on the AlCl 3 /CO 2 /H 2 system identified AlOCl as a major gas phase intermediate which acts as a catalyst to the water-gas shift reaction [7]. Association reactions of the intermediates yield clusters that diffuse to the substrate surface to form the film or serve as nucleus for the formation of particles [23,24].…”
Section: Molecular Size Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent kinetic study on the AlCl 3 /CO 2 /H 2 system identified AlOCl as a major gas phase intermediate which acts as a catalyst to the water-gas shift reaction [7]. Association reactions of the intermediates yield clusters that diffuse to the substrate surface to form the film or serve as nucleus for the formation of particles [23,24].…”
Section: Molecular Size Determinationmentioning
confidence: 99%
“…A commonly used CVD method of producing alumina film is done by reacting AlCl 3 vapor with CO 2 and H 2 at temperatures ranging from 700 to 1000 1C at reduced pressures [5,6]. In this system, the water-gas reaction (CO 2 +H 2 -H 2 O+CO) determines the rate of film formation [6][7][8]. It is critical to control the H 2 O content in the gas mixture because too much water would lead to a powdery deposit due to the rapid reaction of AlCl 3 with water [5].…”
Section: Introductionmentioning
confidence: 99%
“…[28] Important adsorbed intermediate species suggested are AlHO 2 (ad) and AlOCl(ad). Tan et al [29] investigated the homogeneous gas phase kinetics based on the set of rate parameters presented by Catoire and Swihart [30] involving 92 reversible reactions among 32 species. Tan et al [29] suggested AlOCl as the major rate determining intermediate species in the gas phase.…”
Section: Al 2 O 3 Diffusion Barrier Coating By Chemical Vapour Deposimentioning
confidence: 99%
“…Tan et al [29] investigated the homogeneous gas phase kinetics based on the set of rate parameters presented by Catoire and Swihart [30] involving 92 reversible reactions among 32 species. Tan et al [29] suggested AlOCl as the major rate determining intermediate species in the gas phase. Nitodas and Sotirchos, [28] though considering adsorbed AlOCl(ad), did not consider this species taking part in the homogeneous gas phase reactions.…”
Section: Al 2 O 3 Diffusion Barrier Coating By Chemical Vapour Deposimentioning
confidence: 99%
See 1 more Smart Citation